Profitability trends and cycles: structural change in the Mexican economy - Oritiz, C. Ethelberto (2005)
The article presents a heterodox analysis of the rate of profit. The method is especially useful in situations when there is no reliable information on capital stocks. The article assesses two methods in the Mexican economy: a standard Marxian approach and the author's proposed alternative, labeled profitability trends. The new method can als be used to determine sectoral estimates of profitability. - Reproduce.
Keywords: Structural adjustment - Mexico; Mexico - Economic policy; Economic policy